2008
DOI: 10.1002/jbm.a.31895
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sintering on porosity, phase, and surface morphology of spray dried hydroxyapatite microspheres

Abstract: This article deals with the effect of sintering temperature on the physical and chemical characteristics of hydroxyapatite microspheres (HAMs) obtained by spray drying method. A set of specimens were sintered in a conventional furnace at 500-1100 degrees C. The surface morphology, phase composition, size distribution, specific surface area, and porosity were characterized by scanning electron microscope, X-ray diffractometer, laser diffraction particle size analyzer, and specific surface area analyzer, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 27 publications
2
22
0
Order By: Relevance
“…It is known that owing to the low process temperature, spray-dried powders have significant amount of absorbed water [40,41]. In this case, spray-dried pure and Sr-doped HA powders could be lost mass on a large scale up to 150°C.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that owing to the low process temperature, spray-dried powders have significant amount of absorbed water [40,41]. In this case, spray-dried pure and Sr-doped HA powders could be lost mass on a large scale up to 150°C.…”
Section: Resultsmentioning
confidence: 99%
“…Nagao et al has reported that HAp has the ability to absorb therapeutic agents without deactivation and shows regulated release as it biodegrades [22]. The biodegradation speed of HAp can be regulated by calcination temperature [19,23,31]. Spray-drying has been shown to be a good fabrication method for spherical porous HAp powder with a high specific surface area of more than 60 cm 3 /g [23,31].…”
mentioning
confidence: 99%
“…The biodegradation speed of HAp can be regulated by calcination temperature [19,23,31]. Spray-drying has been shown to be a good fabrication method for spherical porous HAp powder with a high specific surface area of more than 60 cm 3 /g [23,31]. Mizushima et al [19] recently reported the possibility of the sustained release of proteins and lipophilic drugs using injectable HAp microparticles.…”
mentioning
confidence: 99%
“…It is shown that the pore size distribution of the hollow HAP microspheres was mainly the mesopores in the range of 2-40 nm, and the mean pore size was 10.5 nm. In general, the widely accepted definitions of the pore size ranges are: micropores o2 nm, mespores 2-50 nm, and macropores 450 nm [21]. The BET and BJH test results showed that the specific surface areas and the total pore volume of hollow HAP microspheres are 120.43 m 2 /g and 0.5614 cm 3 /g, respectively.…”
Section: The Structure and Phase Composition Characterization Of The mentioning
confidence: 98%